Polarization-Independent and Angle-Insensitive Metamaterial Absorber Using 90-Degree-Rotated Split-Ring Resonators - Jia-Qi Feng; Wei-Dong Hu; Qing-Le Zhang; Hua Zong; Hui Huang; Yu-Ting Jin; Yu-Ming Wu; Zhan Xu; Xin Lv; Li-Ming Si (International Journal of Antennas and Propagation)
We present the design, simulation, and measurement of a polarization-independent and angle-insensitive metamaterial absorber (MA) in X-band. Since the unit cell of the MA consists of four subwavelength split-ring resonators with 4-fold symmetric rotation, the MA is insensitive to the variation of both polarization and incident angle of the planar electromagnetic wave. The electromagnetic performances of the MA are studied by full-wave simulations based on finite-element method and the Naval Research Laboratory arch experimental measurements. The electric field distributions are numerically investigated, which confirm the polarization-insensitive property of the MA, as expected from the symmetric nature of the structure. When the incident angles vary from 0 to 45 degrees, the MA remains at full width at half maximum of 0.4 GHz (0.5 GHz) with peak absorptions of 99.9% (95.2%) at 10.27 GHz (10.3 GHz) by simulations (measurements).